THE EFFECTIVENESS OF COMPOMER AND GIC AGAINST PREVENTION IN ENAMEL DEMINERALIZATION - Fadil Abdillah Arifin; Yustisia Puspitasari; Nur Rahmah Hasanuddin; M. Fajrin Wijaya; Sari Aldilawaty (Dentino : Jurnal Kedokteran Gigi, 2021)
Background: Several studies showed that fluoride interferes in the dynamics involved in the development of caries and could present an antimicrobial effect or provide demineralization inhibition or dental remineralization. The development of fluoride-releasing materials can contribute to a preventive of demineralization. GIC and Compomer are restorative materials containing fluoride which can prevent demineralization. Purpose: To analyze the effectiveness of Compomer and GIC against prevention in enamel demineralization. Method: The cavities were made on 18 bovine teeth which grouped into 3 groups, each group consisting of 6 bovine teeth. After the restorative procedures, the teeth were submitted to demineralization and remineralization cycling during 14 days. The sections of the teeth were examined under scanning electron microscope after undergoing pH cycling. The data were analyzed using the Kruskal-Wallis and Tukey Test (p<0.05). Results: GIC group showed the lowest lesion depth of demineralization (10.9883 ± 0.74333) followed by Compomer group (25.4183 ± 3.44268) and Control group (88.9783 ± 3.02495). Conclusion: GIC restorative materials have a better enamel demineralization prevention effect than Compomer. Keywords: compomer, demineralization, fluoride, GIC, remineralization